Using social norms to encourage sustainable behaviour: A meta-analysis - Poškus, Mykolas Simas (Psichologija, 2016)
The aim of this study is to evaluate the effectiveness of using social norms to promote sustainable behaviour. To achieve this aim, a meta-analysis was conducted. Studies published in peer reviewed journals after 1990 that experimentally tested the effectiveness of social norms in promoting sustainable behaviour were included in the analysis. No distinction was made among various populations when selecting studies. Random-effects models were used to calculate the pooled effect sizes. It was found, that social norms can be effectively used in promoting sustainable behaviour (d = 0.35, 95% CI [0.13, 0.57]), the effect is highest in cases that imitate real-life situations (d = 0.52, 95% CI [0.38, 0.65]), and remains significant when comparing normative interventions against alternative appeals that are aimed at promoting sustainable behaviour (d = 0.18, 95% CI [0.03, 0.32]). The article concludes that normative interventions are an effective way of promoting sustainable behaviour. Those who are engaged in promoting sustainable behaviour should strongly consider using social norms as a means to their goals as it is an effective and evidence-based way of promoting desired behaviour.
Keywords: social norms; descriptive norms; injunctive norms; sustainable behaviour